Physiological and molecular mechanisms of tolerance to hypoxia and oxygen deficiency resistance markers - Silina, Maria; Dzhalilova, Dzhuliia; Fokichev, Nikolai; Makarova, Olga (Frontiers in Molecular Biosciences, 2025)
Humans and laboratory animals differ in their resistance to hypoxia, which affects the severity of inflammatory diseases and the rate of tumor progression. Therefore, it is necessary to search for methods for assessing the initial tolerance to oxygen deficiency and the risks of developing acute mountain sickness without direct hypoxia exposure on the organism. The literature describes assessments of oxygen deficiency tolerance assessing based on physiological and molecular parameters. The limitations of such methods include the need of expensive equipment use and highly qualified specialists involvement. In addition, in the studies presented in this review, the altitude, time and methods for achieving it, as well as the frequency of assessing the severity of acute mountain sickness varied significantly. It is necessary to continue research aimed at investigating biomarkers of tolerance to oxygen deficiency without direct hypoxia exposure using instrumental and laboratory diagnostics. This will allow developing new approaches for personalized prevention, diagnosis and treatment of inflammatory diseases and malignancies and, accordingly, improve the quality of life.